2010
DOI: 10.1002/adfm.200902273
|View full text |Cite
|
Sign up to set email alerts
|

Temperature‐Resolved Local and Macroscopic Charge Carrier Transport in Thin P3HT Layers

Abstract: Previous investigations of the field‐effect mobility in poly(3‐hexylthiophene) (P3HT) layers revealed a strong dependence on molecular weight (MW), which was shown to be closely related to layer morphology. Here, charge carrier mobilities of two P3HT MW fractions (medium‐MW: Mn = 7 200 g mol−1; high‐MW: Mn = 27 000 g mol−1) are probed as a function of temperature at a local and a macroscopic length scale, using pulse‐radiolysis time‐resolved microwave conductivity (PR‐TRMC) and organic field‐effect transistor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
177
1
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(195 citation statements)
references
References 52 publications
16
177
1
1
Order By: Relevance
“…5 As the temperature decreased, σ abs slightly decreased (Fig.2), reaching a value of ~370 cm -1 (0.046 eV) at 100 K (for the A 1 band). This suggests that line broadening in the absorption spectrum of ADT-TES-F films in the studied temperature range is dominated by a weakly temperature-dependent static disorder, which has a considerable contribution from solid-state defects such as temperature-dependent due to several factors; 36 for example, in P3dHT films W decreased from 0.22 eV to 0.14 eV as the temperature decreased from 120°C to 30°C, 36 due to temperature-induced changes in the spatial correlation length l 0 . 30,41 From the data in Fig.2(a), we obtained W abs ≈ 0.06 eV at 298 K, 0.05 eV at 225 K, and 0.013 eV at 100…”
Section: Optical Absorptionmentioning
confidence: 88%
See 1 more Smart Citation
“…5 As the temperature decreased, σ abs slightly decreased (Fig.2), reaching a value of ~370 cm -1 (0.046 eV) at 100 K (for the A 1 band). This suggests that line broadening in the absorption spectrum of ADT-TES-F films in the studied temperature range is dominated by a weakly temperature-dependent static disorder, which has a considerable contribution from solid-state defects such as temperature-dependent due to several factors; 36 for example, in P3dHT films W decreased from 0.22 eV to 0.14 eV as the temperature decreased from 120°C to 30°C, 36 due to temperature-induced changes in the spatial correlation length l 0 . 30,41 From the data in Fig.2(a), we obtained W abs ≈ 0.06 eV at 298 K, 0.05 eV at 225 K, and 0.013 eV at 100…”
Section: Optical Absorptionmentioning
confidence: 88%
“…9,26 At 298 K (room temperature), a red-shift of the film spectrum with respect to that of isolated ADT-TES-F molecules, D ≈ 870 cm -1 (~0.108 eV) in Fig.2(a), was observed and attributed to enhanced Coulomb interaction of the molecule with its surrounding environment and exchange interactions between translationally equivalent molecules. 5,[27][28][29][30] 26,34,36 and attributed to freezing out of the torsional and librational modes, which promotes exciton delocalization, as well as to a thermal contraction of the lattice leading to an increase in nonresonant intermolecular interactions (which would increase the parameter D in Fig.2(a)). 30 In ADT-TES-F films, these effects were relatively strong, as the peak red-shift rate of ~2×10 -4 eV/K in ADT-TES-F films was a factor of ~2-5 higher than that in, for example, conjugated polymers 26 and PTCDA crystals.…”
Section: Optical Absorptionmentioning
confidence: 99%
“…However, different groups have shown that a strong correlation exists between charge transport and nanomorphology/ crystallinity of the P3HT films [41][42][43][44][45][46][47][48][49] which depend crucially on the thin-film processing conditions. The morphology and crystallinity of P3HT thin films is affected by (i) the thin-film preparation method (drop-casting, spin coating, inkjet printing), (ii) the nature of the substrates and (iii) the macromolecular parameters, for example, average molecular weight, regioregularity and polydispersity (PDI) of the polymer.…”
Section: Morphology and Structure In Thin Filmsmentioning
confidence: 99%
“…Furthermore, molecular tailoring of organic compounds via chemical modification can achieve high field-effect performance of the active semiconducting layers. For example, fused acene [18], oligothiophene [19], tetrathiafulvalene derivatives [20] and conjugated polymers [21] exhibit field-effect mobilities much larger than 0.1 cm 2 V −1 s −1 . However, the chemical and electrical stabilities of these OFETs, and consequent degradation in on-current, threshold voltage and field-effect mobility under air exposure remain a problem.…”
Section: Introductionmentioning
confidence: 99%